2020
DOI: 10.1108/jopp-07-2019-0044
|View full text |Cite
|
Sign up to set email alerts
|

Implementing sustainable procurement in the United Arab Emirates public sector

Abstract: Purpose Despite making significant strides in transforming its environmental outlook over the past few years and promoting sustainable procurement (SP) in the public sector, the United Arab Emirates (UAE) is still facing serious challenges in moving up the global sustainability ranks. Thus, this study aims to assess and prioritize critical factors, including cost, organization, innovation capability, stakeholder, culture and market-related factors, and their respective sub-factors for the implementation of SP,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…However, negative emphasis for suppliers, predominantly considered little salient. Nevertheless, the importance of the suppliers is highlighted in the work of Brammer and Walker (2011), Meehan and Bryde (2011), Witjes and Lozano (2016), Guarnieri and Gomes (2019) and Al Nuaimi et al (2020). Experts have not ignored the importance of suppliers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, negative emphasis for suppliers, predominantly considered little salient. Nevertheless, the importance of the suppliers is highlighted in the work of Brammer and Walker (2011), Meehan and Bryde (2011), Witjes and Lozano (2016), Guarnieri and Gomes (2019) and Al Nuaimi et al (2020). Experts have not ignored the importance of suppliers.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the suppliers, they were considered to be low salient. This could be an indicator of the supplier market's incapacity (even though temporary) to meet new demands for sustainable products and services, which, in turn, could be because of the absence of a broader and more inclusive structuring policy, one that could allow the government to urge suppliers to participate collaboratively (Meehan and Bryde, 2011;Witjes and Lozano, 2016;Guarnieri and Gomes, 2019;Al Nuaimi et al, 2020) in the development of policies and to properly inform them about the new preferences of a market with great purchasing power and ample prospects for growth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In United Arabs of Emirates (UAE) a study declared the influence of green products prices, and it was revealed by the authors that the prices of pro-environmental products ranked as the highest critical factor impacting the proenvironmental behaviors, and available green products at high prices force consumers' behaviors renitent to green procurements regardless how beneficial they were (Al Nuaimi et al [11]).…”
Section: Introductionmentioning
confidence: 99%